Zizyphus lotus L. (Desf.) modulates antioxidant activity and human T-cell proliferation - Belarbi Meriem; Simonin Anne-Marie; Yessoufou Akadiri; Hichami Aziz; Benammar Chahid; Allali Hocine; Khan Naim A (BMC, 2010)
Abstract Background Zizyphus lotus L. (Desf.) also known as Jujube, is a deciduous shrub which belongs to Rhamnaceae family. This plant is used in Algerian traditional medicine for its anti-diabetic, sedative, analgesic, anti-inflammatory and hypoglycaemic activities. In the present study, we determined the concentrations of different vitamins (vitamin A, C and E) and fatty acids in root, stem, leaves, fruit pulp and seed of Zizyphus lotus L. (Desf.) and assessed the effects of their aqueous extracts on antioxidant status and human T-cell proliferation. Methods Aqueous filtrates from different parts, i.e, root, leaf, stem, fruit pulp and seed, of Zizyphus lotus L. (Desf.) were prepared. Vitamin C levels were determined by precipitating with 10% trichloroacetic acid and vitamin A and E were assessed by HPLC. Lipid composition of these extracts was determined by gas-liquid chromatography. Anti-oxidant capacity was evaluated by using anti-radical resistance kit [Kit Radicaux Libres (KRL@; Kirial International SA, Couternon, France)]. T-cell blastogenesis was assessed by the incorporation of 3H-thymidine. IL-2 gene expression was evaluated by RT-qPCR. Results Our results show that fruit pulp contained higher vitamin A and C contents than other parts of the plant. Furthermore, the fruit pulp was the richest source of linoleic acid (18:2n-6), a precursor of n-6 fatty acids. Fruit seeds possessed higher vitamin C levels than leaves, roots and stem. The leaves were the richest source of vitamin E and linolenic acid (18:3n-3), a precursor of n-3 fatty acids. The antioxidant capacity of the different extracts, measured by KRL@ test, was as follows: pulp < seed<leaf<root < stem. As far as T-cell proliferation is concerned, we observed that the different extracts of Zizyphus lotus L. (Desf.) exerted immunosuppressive effects. Conclusion Seed extracts exerted the most potent immunosuppressive effects on T cell proliferation and IL-2 mRNA expression. The results of the present study are discussed in the light of their use to modulate the immune-mediated diseases.